2021
DOI: 10.3389/fcvm.2021.768026
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Related Vascular and Cardiac Benefits in Obesity: Is There a Role for an Epigenetically Regulated Mechanism?

Abstract: In obesity, several epigenetic modifications, including histones remodeling, DNA methylation, and microRNAs, could accumulate and determine increased expression of inflammatory molecules, the adipokines, that in turn might induce or accelerate the onset and development of cardiovascular and metabolic disorders. In order to better clarify the potential epigenetic mechanisms underlying the modulation of the inflammatory response by adipokines, the DNA methylation profile in peripheral leukocytes of the promoter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…On the other hand, Macrophages and lymphocytes secrete TNFα in response to cell damage. Our observation is concomitant to previous studies where IL6 and TNFα were found to be elevated in patients with lipid abnormalities and insulin resistance ( Pickup et al, 1997 ; Bahceci et al, 2007 ; Popko et al, 2010 ; Fontanella et al, 2021 ).…”
Section: Resultssupporting
confidence: 91%
“…On the other hand, Macrophages and lymphocytes secrete TNFα in response to cell damage. Our observation is concomitant to previous studies where IL6 and TNFα were found to be elevated in patients with lipid abnormalities and insulin resistance ( Pickup et al, 1997 ; Bahceci et al, 2007 ; Popko et al, 2010 ; Fontanella et al, 2021 ).…”
Section: Resultssupporting
confidence: 91%
“…Up to now, many risk factors are reported to contribute to atherosclerosis, including smoking, hypercholesterolemia, hypertension, hyperglycemia, genetic factors, and epigenetic factors [11][12][13][14]. The N6-methyladenosine (m6A) modi cation is the most abundant epi-transcriptomic modi cation in mRNA, and plays important roles in various diseases, such as obesity, cancers, hypertension and viral infection through regulating RNA stability, export, splicing or translation [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Age, stage of the disease, and several other factors influence the levels of OPG, justifying such discrepant results between studies. Furthermore, autoantibodies to osteoprotegerin are associated with increased bone resorption in RA, with OPG antibody-positive patients having longer disease duration and activity and higher levels of bone resorption markers [ 66 , 67 , 70 , 71 , 72 ].…”
Section: General Aspects Of Ra and The Role Of Myokines Osteokines Ad...mentioning
confidence: 99%
“…In musculoskeletal disorders such as RA, adipokines were described as modulators of bones, synovial membranes, and cartilages activities. Additionally, higher levels of adipokines are encountered in both serum and synovial fluid in patients with RA than in those who are healthy [ 6 , 7 , 72 , 74 ].…”
Section: General Aspects Of Ra and The Role Of Myokines Osteokines Ad...mentioning
confidence: 99%